2002
DOI: 10.1002/eat.10027
|View full text |Cite
|
Sign up to set email alerts
|

Body image treatment within an inpatient program for anorexia nervosa: The role of mirror exposure in the desensitization process

Abstract: Mirror confrontation is a more effective form of exposure because of the strong emotional response it elicits. Patients' pronounced emotional response to this exercise allowed easier identification of the affective and behavioral components of body dissatisfaction and more cogent links into a developmental body image timeline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(83 citation statements)
references
References 10 publications
(9 reference statements)
3
75
0
4
Order By: Relevance
“…In cognitive-behavioral treatment for eating disorders, body exposure techniques are applied, leading patients to focus systematically on each body part to correct their distorted view of themselves. 34,[53][54][55] Taking the results of the present study into account, it could be promising not only to restrict these exposure techniques to the static component of body image, but also to confront patients with their own motion patterns. Providing the patients with video feedback concerning their real motion patterns might correct their distorted view of themselves and thus contribute to the establishment of a positive body image.…”
Section: Resultsmentioning
confidence: 98%
“…In cognitive-behavioral treatment for eating disorders, body exposure techniques are applied, leading patients to focus systematically on each body part to correct their distorted view of themselves. 34,[53][54][55] Taking the results of the present study into account, it could be promising not only to restrict these exposure techniques to the static component of body image, but also to confront patients with their own motion patterns. Providing the patients with video feedback concerning their real motion patterns might correct their distorted view of themselves and thus contribute to the establishment of a positive body image.…”
Section: Resultsmentioning
confidence: 98%
“…It is essential that the selection criteria for admission and the main treatment program remain the same (''treatment as usual''). Examples of this research strategy are the comparison of ''strict'' versus ''lenient'' contingency management (Touyz, 1998), behavioral contracts with varying degrees of minimum weight gain required (Solanto et al, 1994), day hospital programs of different lengths (Olmsted, McFarlane, Molleken, & Kaplan, 2001), body image treatment with or without confrontational procedures (Fernández & Vandereycken, 1994;Key et al, 2002), family therapy versus family group psychoeducation (Greist, Heinmaa, Stephens, Davis, & Katzman, 2000;Vanderlinden & Vandereycken, 1987), and cognitive-behavior group therapy versus a psychoeducation group (Wiseman, Sunday, Klapper, Klein, & Halmi, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies in eating‐disordered and non‐eating‐disordered women have suggested that being exposed to their own body in a mirror (mirror exposure therapy) can help desensitize a patient to their body appearance (Delinsky & Wilson, 2006; Key et al ., 2002; Vocks, Wachter, Wucherer, & Kosfelder, 2008). However, this does not directly tackle the issue of body size overestimation.…”
Section: Introductionmentioning
confidence: 99%